Curriculum Design for Entrepreneurship Education in Pesantren: Strengthening Student Competencies in the Era of 5.0 - Al Mukaromah Hidayat; Mega Melani Ramadani (PT Mutiara Bustan Ilmu, 2024)
This study explores the design and implementation of an entrepreneurial curriculum within pesantren, focusing on enhancing student competencies in the context of Industry 5.0. The research employs a qualitative approach, involving interviews, surveys, and observations to gather insights from students, educators, and administrators. Key elements identified in the curriculum design include competency-based education, the integration of religious values, and the incorporation of technology in learning. The findings indicate significant improvements in students' entrepreneurial skills, attitudes, and motivation following the curriculum's implementation. Furthermore, challenges faced during the design and execution phases are discussed, along with recommendations for future curriculum development. This study contributes to the understanding of effective entrepreneurship education in Islamic boarding schools and offers valuable insights for educators and policymakers seeking to enhance entrepreneurial competencies among students.